Coronavirus 2019, Thrombocytopenia and HELLP Syndrome: Association or Coincidence? - Luiz Felipe Bagnatori Braga; Nelson Sass (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract The present report describes the case of a 31-year-old primigravida, with dichorionic twins at 31 weeks. She presented with history of myalgia, jaundice, and abdominal discomfort. No flu-like symptoms as fever or cough. She was not aware of exposure to COVID-19. Normal blood pressure and O2 saturation. Laboratory tests showed platelet count of 218,000 mm3, alanine aminotransferase (ALT) 558 IU and serum creatinine 2.3 mg/dl. Doppler ultrasound in one twin was compatible with brain sparing. Partial hemolysis, elevated liver enzymes, low platelet count (HELLP) syndrome was the hypothesis, and a cesarean section was performed. On day 2, the white-cell count reached 33,730, with decreased consciousness and mild respiratory distress. Tomography revealed both lungs with ground-glass opacities. Swab for COVID-19 polymerase chain reaction (PCR) was positive. Thrombocytopenia in patients with COVID-19 appears to be multifactorial, similar to what occurs in preeclampsia and HELLP syndrome. We assume that the synergism of these pathophysiological mechanisms could accelerate the compromise of maternal conditions and could be a warning to the obstetric practice.